EQUAL GENDER REPRESENTATION IN EFL INSTRUCTIONAL MATERIALS DURING EMERGENCY REMOTE LEARNING - Hilda Triyaswati; Ive Emaliana (International Journal of Humanity Studies (IJHS), 2021)
Gender representations in EFL instructional materials can be given less attention amid covid-19 pandemic because there are abundant resources offered in online learning. The current paper aims to investigate a measurement to determine whether males and females are portrayed equally in EFL instructional materials, as proposed in RUU No. 81 A of 2013 the Republic of Indonesia's Ministry of Education and Culture which stated: “The curriculum should be oriented toward the production of good manners and a fair attitude, with a focus on gender equality". Employing library research method, researchers attempt to achieve this by examining ten experts’ theories which postulate equal representations of gender in EFL textbooks, namely (Dominguez 2003), Cohen, L Manion (1992), (Porreca 1984), Stockdale (2006), (Sovič and Hus 2015), (Hall 2014),  (Gharbavi and Mousavi 2012), Holmqvist and Gjorup (2006), Nofal and Qawar (2015), and Chung (2014). The findings from the analysis indicate that gender representations in learning materials measured through language items and illustrations showed inequal and further complete sub dimensions descriptions are elucidated in the discussions. Pedagogical implications of selecting and developing instructional materials, which represent gender equality, are explored more to foster effective emergency remote learning